Theoretical and experimental characterization of Sn-based hydroxyapatites doped with Bi - Korkmaz, A. Aksogan; Ahmed, Lana Omar; Kareem, Rebaz Obaid; Kebiroglu, Hanifi; Ates, Tankut; Bulut, Niyazi; Ates, Burhan (Springer, 2022)
This is the first report, including both theoretical and experimental results, on Bi and Sn co-doped hydroxyapatite (HAp) structures. Sn content was kept at a constant amount of 0.22 at.%, and Bi content was changed from 0 to 0.44 at.% by using the steps of 0.11at.%. Theoretical results from density functional theory (DFT) calculations revealed an increase in density from 3.154 g cm(-3) to 3.179 g cm(-3), as well as gradual decreases in the bandgap from 4.5993 eV to 4.4288 eV and the linear absorption coefficient. The spectroscopic data obtained from both Raman and Fourier transform infrared (FTIR) spectra confirmed the HAp structure for all the samples. The thermal behavior and morphology, as well as all X-ray diffraction (XRD) related parameters, were all considerably impacted by Bi-content. In vitro assays showed that all the samples can be accepted as the biocompatible materials.
Keywords: Hydroxyapatite; X-ray diffraction; Spectroscopic analysis; Bandgap